Mutation analysis of apyrase gene of shigella jlexneri - towards the development of vaccine strain - Aun, Seah Chin (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2005)
The discovery of the microbe Shigella was dated back about I 00 years ago by a scientist named Kiyoshi Shiga. Virulent Shigella spp. are known to cause bacillary dysentery (shigeilosis) in humans which is characterized by the passage of bloody stools. According to the WHO, an estimated of 1.1 million global population dies every year is due to the disease shigellosis. Despite much studies were carried out regarding this pathogenic bacteria, no vaccine is available for this infectious disease. Literatures have postulated that one of the virulence genes is the apy gene which encodes for apyrase. Therefore, in this study the gene of interest is the apy gene. We have successfully mutated the apy gene with a kanamycin gene cassette (aphA) and subcloned the construct into a conjugative suicide vector.